A Historical Study on The Kingdom of Bahrain: The importance of the Site and Its Role in Bahrain’s Modern and Contemporary History - Al-Jazi, Mohammad Abdul-Hadi Saleh (Journal of History Culture and Art Research, 2020)
This study highlights the important aspects of the geography of the Kingdom of Bahrain. It also shows the importance of the site, the demography of the region, the distribution of population, and the most important cities in the Kingdom of Bahrain. Firstly, the study deals with the geographical location of the Kingdom of Bahrain; secondly, it shows the importance of the site with respect to its geographical location; and thirdly, analyzes the most important geographical features, shapes and topography. The study also examines the prevailing climate and the most important natural resources found there. The study also referred to the population census in it, the census of the indigenous population the proportion of foreigners and the percentage of Sunnis and Shiites in Bahrain. At the end of the study, the most important cities in the Kingdom of Bahrain were also summarized. The study, as a whole, talks about the most important historical features of the Kingdom of Bahrain.